A numerical study on mesoscale simulation of quartzite and sandstone under shock loading. (October 2017) - Durr, Nathanaël; Sauer, Martin; Hiermaier, Stefan
Highlights: A mesoscale model for quartzite and sandstone under shock compression is developed. Two numerical FE and SPH schemes are complementarily employed. Effects of porosity and quartz shear strength on pore collapse dynamics are studied. Effects of mesoscale parameters on macroscopic shock Hugoniots are investigated. Hugoniot shock data is compared to literature and model improvements are proposed. Abstract: In this paper, we present two numerical models for the mesoscale (grain scale) simulation of planar shock waves in quartzite and sandstone using the in-house hydrocode SOPHIA. The models are compared in terms of their capability to represent physical mechanisms, such as phase transitions in quartz and pore collapse in sandstone, and they are validated by comparison to literature data. The study is part of the MEMIN (Multidisciplinary Experimental and Modeling Impact Research Network) project, which is devoted to the experimental and numerical investigation of the effects of meteorite impact on geological materials from laboratory scale to natural scale. The first model is based on the Smoothed Particle Hydrodynamics (SPH) method. Simulations with rather simplified structures in planar symmetry are presented. The model is used to investigate basic effects of porosity, pore geometry and water saturation. The second model presented is a more detailed, three-dimensional Finite Element (FE) model. With this model, the effects of grain anisotropy and different types of shear strength modeling are studied. In a parameter study, we investigate the influence of these parameters on shock Hugoniot relations, such as shock velocity ( Us ) vs. particle velocity ( Up ) and compressive longitudinal stress ( σL ) vs. Up . Finally, the models are compared and the specific advantages and disadvantages of the different modeling variants are outlined.